Assessment of asymmetrical lower limb loading in the short-track speed skaters - Kaczorowska, A.; Dajczak, M.; Mroczek, A.; Lepsy, W. (Central European Journal of Sport Sciences and Medicine, 2023)
Short-track speed skaters who regularly participate in training are exposed to the occurrence of asymmetry in the lower limb loading. Objective. The study aimed to assess the symmetry of the lower limb loading in short track skaters and the relationship between age, training experience and anthropometric variables and symmetry of lower limb loading. Methods. The examined group consisted of 20 short-track speed skaters (12 men and 8 women), and the control group comprised 28 university students (14 men and 14 women). Two scales were used to assess the symmetry of lower limb loading, and the lower limb's loading symmetry index (LSI) was calculated. Results. In the studied groups 65% of skaters and 82% of students have LSI within the normal range. Most short-track speed skaters (85%) put weight on the right lower limb, and there was no clear trend among students (p < 0.001). In the group of skaters, the majority of men (83%) properly loaded their lower limbs, compared to 37.5% of women (p = 0.036). In short-track speed skaters, positive correlations were found between LSI and the age and length of training. Conclusions. Long-term asymmetric loading of the lower limbs in short-track speed skaters causes the advantage of the load on the right lower limb and increases the asymmetry of the load on the lower limbs, especially in women.